Water Splitting on Multifaceted SrTiO3 Nanocrystals: Computational Study - Maksim Sokolov (MDPI AG, 2021)
Recent experimental findings suggest that strontium titanate SrTiO3 (STO) photocatalytic activity for water splitting could be improved by creating multifaceted nanoparticles. To understand the underlying mechanisms and energetics, the model for faceted nanoparticles was created. The multifaceted nanoparticles’ surface is considered by us as a combination of flat and “stepped” facets. Ab initio calculations of the adsorption of water and oxygen evolution reaction (OER) intermediates were performed. Our findings suggest that the “slope” part of the step showed a natural similarity to the flat surface, whereas the “ridge” part exhibited significantly different adsorption configurations. On the “slope” region, both molecular and dissociative adsorption modes were possible, whereas on the “ridge”, only dissociative adsorption was observed. Water adsorption energies on the “ridge” ( <semantics>−1.50</semantics> eV) were significantly higher than on the “slope” ( <semantics>−0.76</semantics> eV molecular; <semantics>−0.83</semantics> eV dissociative) or flat surface ( <semantics>−0.79</semantics> eV molecular; <semantics>−1.09</semantics> eV dissociative).